2015
DOI: 10.1097/md.0000000000000535
|View full text |Cite
|
Sign up to set email alerts
|

Information-seeking Behavior During Residency Is Associated With Quality of Theoretical Learning, Academic Career Achievements, and Evidence-based Medical Practice

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…This is consistent with the study by Oussalah et al which showed that enrollment in a PhD or a research Master is an independent predictor of PubMed searching skill and knowledge of main journals. 21 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the study by Oussalah et al which showed that enrollment in a PhD or a research Master is an independent predictor of PubMed searching skill and knowledge of main journals. 21 …”
Section: Discussionmentioning
confidence: 99%
“…These factors can either strengthen or detract from the focus on resolving clinical issues. Textbooks3 42 45 49 56–67 and guidelines64 66 68 69 are frequently used due to their high credibility. Additionally, Google is employed for its accessibility to a wide range of information resources 62 70.…”
Section: Discussionmentioning
confidence: 99%
“…Residency programs are designed to train resident physicians in delivering clinical care to patients and learning their chosen specialties at the same time [1]. Many residents, while caring for patients during rounds and clinics, encounter several clinical questions that need to be answered [2].…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, the concept of informationseeking behavior was introduced for the first time in the medical literature. It is defined as the necessity to acquire information in response to an individual's realization of a gap in his knowledge [1]. Accessibility, availability of information, and organizational factors contribute to health information-seeking behavior.…”
Section: Introductionmentioning
confidence: 99%